Analisis Pengaruh Perubahan Kerapatan Vegetasi Terhadap Suhu Permukaan Karena Kegiatan Pertambangan Menggunakan Citra Satelit Multiwaktu (studi kasus: PT. AMMAN MINERAL NUSA TENGGARA) - Bayu Wisnu Putra; Djurdjani Djurdjani (Universitas Gadjah Mada, 2020)
PT.Amman Mineral Nusa Tenggara (PT.AMNT) is an Indonesian mining company that operates the Batu Hijau mine. Mining activities can cause a decrease in vegetation cover and can have an impact on increasing surface temperature. This study aims to determine how the impact of mining activities on vegetation density and surface temperature. The change in vegetation density and surface temperature in the mining area can be detected by processing of remote sensing satellite imagery with different data recording times. The data used are five Landsat satellite imagery in 1998, 2004, 2008, 2014 and 2018. Vegetation index extraction process is carried out using the NDVI (Normalized Difference Vegetation Index) formula. While surface temperature extraction process is carried out using the Mono-window Brightness Temperature method. The results of the extraction process are then used to analyze the effect of vegetation density changes on surface temperature. The results of this study indicate that the vegetation density in the mining area has decreased and the average surface temperature has increased. The results of the correlation analysis showed that the decrease in the level of vegetation density caused the increase in surface temperature in the mining area of PT.AMNT.